2022
DOI: 10.3390/ijerph19106030
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of FTO, FABP2, LEP, LEPR, and MC4R Genes on Obesity Parameters in Physically Active Caucasian Men

Abstract: Obesity is a complex multifactorial abnormality that has a well-confirmed genetic basis. However, the problem still lies in identifying the polymorphisms linked to body mass and composition. Therefore, this study aimed to analyze associations between FTO (rs9939609), FABP2 (rs1799883), and LEP (rs2167270), LEPR (rs1137101), and MC4R (rs17782313) polymorphisms and obesity-related parameters. Unrelated Caucasian males (n = 165) were recruited. All participants had similar physical activity levels. The participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Inclusion criteria: Healthy participants aged between 40 and 60 years; BMI of 25 or greater and no more than a 3% change in body mass within the last three months; Presence of at least one minor allele in any of the following genetic polymorphisms: FTO (rs9939609; T > A), LEP (rs2167270; G > A), LEPR (rs1137101; A > G; Gln223Arg), and MC4R (rs17782313; T > C) [ 38 ]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion criteria: Healthy participants aged between 40 and 60 years; BMI of 25 or greater and no more than a 3% change in body mass within the last three months; Presence of at least one minor allele in any of the following genetic polymorphisms: FTO (rs9939609; T > A), LEP (rs2167270; G > A), LEPR (rs1137101; A > G; Gln223Arg), and MC4R (rs17782313; T > C) [ 38 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Presence of at least one minor allele in any of the following genetic polymorphisms: FTO (rs9939609; T > A), LEP (rs2167270; G > A), LEPR (rs1137101; A > G; Gln223Arg), and MC4R (rs17782313; T > C) [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GWAS studies found a strong association between common variants in monogenic-obesity-causing genes and the development of common obesity. For example, the SNP rs17782313, located 188 kb downstream of the MC4R gene, was found to be significantly associated with a higher BMI, higher fat mass, and elevated risk of common obesity in various populations with different genetic backgrounds, including Caucasians, Mexican, Chinese, and Iranian [206][207][208][209][210][211][212][213][214]. The SNP is suggestively involved in MC4R expression and translation regulation, and consequently affects food intake and nutrient preference [215,216].…”
mentioning
confidence: 99%